Pengenalan Literasi Keuangan Bagi Siswa Sekolah Dasar dalam Merencanakan Masa Depan - Ainiyah, Nur; Zusyana Dewi, Ratnaningrum; Asyarin Hayau Lailin, Moch. Ichdah (Fakultas Ekonomi Universitas Islam Majapahit, 2024)
Through financial education, children are empowered to make wise decisions about money, save, and even understand the importance of sharing in a financial context. For young people to leave school without the basic skills to manage their personal financial affairs, this puts them at high risk of being unable to plan their financial future responsibly. This education can be carried out by holding outreach activities. This activity is carried out in two stages, namely preparation stages by identifying objectives, analyzing target audiences, choosing the right communication method, designing the right material so that it is easy to understand, determining the right location and time. The implementation stage is carried out by providing understanding and building discourse for students to increase their understanding of good financial management in order to achieve a prosperous future. The results of this activity make sixth grade students at SD Negeri Awang-Awang Mojosari more financially literate, they can develop the skills and knowledge to navigate the ins and outs of the basic financial system, make the right decisions regarding saving/investing. This activity succeeded in creating an environment that supports positive learning and provides a strong initial foundation for understanding financial literacy among Awang-Awang Mojosari Elementary School students.